Bridging the gap: a bibliometric analysis of the EPI and its role in addressing environmental challenges - Muhammed Haziq Muhammed Nor; Mohd Aftar Abu Bakar; Wan Hanna Melini Wan Mohtar; Lee, Bernard Kok Bang; Noratiqah Mohd Ariff (Penerbit Universiti Kebangsaan Malaysia, 2025)
Organizations have increasingly recognized the importance of sustainability in recent decades. As a result, they have made significant efforts to develop specific metrics for the purpose of accurately evaluating sustainability. Environmental sustainability metrics are gaining popularity due to their significance in combating the climate crisis. These metrics help organizations that prioritize environmental initiatives to assess progress, monitor goals, and verify effectiveness by focusing on waste reduction and energy efficiency. The Environmental Performance Index (EPI) is a globally recognized tool used to evaluate the progress made by 180 countries in addressing climate change, environmental health, and ecosystem vitality. However, the EPI encounters several challenges in its role as the main indicator of environmental performance which include data gaps and inconsistencies in methodology. Quantifying the scientific production, quality, and impact of the EPI is crucial in assessing its relevance in academia, despite its current limitations. Therefore, a comprehensive bibliometric analysis has been conducted on 393 publications from the Scopus database, related to EPI. The bibliometric analysis explored on recent developments in this field, the diversity of countries and authors collaborations and an overview of the most frequently cited documents. The results showed that previous studies do not provide enough insights to resolve limitations as a whole, which may allow others to improve EPI reliability. The paper concludes with valuable insights on how modifying the existing metric while addressing its limitations based on previous research can change the future of EPI studies and improve their academic relevance.